Blood and Social System: Battle of Purity and Impurity - Baniya, Lina (Nepalese Journal of Society and Culture, 2025)
This ethnographic research examines the female subjectivity regarding their menstrual understanding, perceptions, restrictions and practices within the prevailing Hindu and Buddhist notions of purity and pollution. Local Dhami, priest, politician and social workers reported that they are uncertain about the impurity but cannot say “it is pure”, as the cultural, religious and social systems have created confusion. When a lady is menstruating, she is not allowed to contact anyone. If someone does, they must be cleansed by bathing and drinking cow urine. Because it is thought that the pants may die or grow deformed, she is not permitted to touch pregnant ladies or green hair (Water Aid in Nepal, 2009). In contrast, Buddhist sects differ from Hindu religions. Buddhism has a pure view of menstruation. I have captured mixed views on these practices, debating whether they are “pure or impure.” Numerous voices advocate for change; however, it remains unclear how the battle between purity and impurity will be resolved. I have used four different data collection methods, with focus group discussions and personal interviews, across four provinces and seven districts.